An assessment of the artificial modelling elements approach to the pressure-driven analysis of water distribution networks - Tanyimboh, Tiku T.; Sivakumar, P.; Gorev, Nikolai B.; Nivedita, S.; Suribabu, C. R.; Gupta, Rajesh (IWA Publishing, 2023)
EPANET 2.2 is a newly introduced upgraded version of EPANET 2 that can be used for both pressure-driven analysis (PDA) and demanddriven analysis (DDA) of water distribution networks. Moreover, it has certain limitations concerning the minimum and required pressure head parameters used for PDA, which leads to inaccurate simulation results. Another limitation of the PDA option of EPANET 2.2 is its inability to simultaneously consider pressure-dependent demands with pressure-independent fire demands. In this article, the reason for the spurious convergence is identified, and it is shown that the spurious convergence of EPANET 2.2 can be addressed by extending the energy balance convergence criterion to include the virtual demand links employed in the EPANET 2.2 formulation of PDA. On the other hand, interest in the methods that use artificial modelling elements in EPANET 2 for PDA is increasing rapidly. The implementation of the method presented in this paper (termed the alternative PDA approach) allows an extended period simulation of large networks with complex demand patterns, multiple tanks, reservoirs, pumps, valves, and thousands of pipes. Two benchmark networks and two real-world networks were analysed by both the alternative PDA approach and EPANET 2.2 and the results were compared.
Keywords: Alternative pressure-driven analysis; EPANET 2.2; Pressure-deficient network; Simulation models; Water distribution network; SDG-17: Partnerships for the goals